2019
DOI: 10.35609/gjbssr.2019.7.2(2)
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Faced by Malaysian Parents in Caregiving of a Child with Disabilities

Abstract: Objective - Caregiving of a child with special needs can increase the cost of raising the child and parent’s stress. These two issues are commonly experienced by a parent who care for their special needs child themselves and the thought of challenges are different based on the disability of the child. Methodology/Technique – The challenges of raising a child with disability make it necessary for parents to work harder to to meet the cost of treatment. Meanwhile, levels of stress among those parents are underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…In addition to caretaking demands, many studies suggested that financial demands in caring for children with disabilities are significant stressors for parents (Chen et al, 2020;Ren et al, 2020;Vonneilich et al, 2016). Compared with children with normal development, children with any disability tend to need special medical treatment, education, and equipment, resulting in a significantly higher financial burden for the parents (Bahry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to caretaking demands, many studies suggested that financial demands in caring for children with disabilities are significant stressors for parents (Chen et al, 2020;Ren et al, 2020;Vonneilich et al, 2016). Compared with children with normal development, children with any disability tend to need special medical treatment, education, and equipment, resulting in a significantly higher financial burden for the parents (Bahry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…(Babic & Leutar, 2014). Parents are also often concerned and worried by the density of caring responsibilities that been required time and a lot of work and energy and parent also must be available most of time to cater the need and meet the daily needs of the child which this might affect their career (Bahry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore it is also proved that having special need children in the family, parents social life is affected or disrupted due to the amount of time spend catering and monitoring the children. Some may avoid going to social gathering due to the disturbing and uncontrollable behavior of their children (Bahry et al, 2019).…”
Section: Introductionmentioning
confidence: 99%